Nivel de conocimiento, actitudes, y practicas preventivas sobre el VIH/SIDA en los usuarios del centro del adulto mayor del Hospital Essalud Tarapoto. Periodo Abril – Agosto 2012. - Tuanama Benites, Erika Tatiana (2012)
This paper's main objective is "Detennining the level knowledge, attitudes and preventive practices on HIV I AIDS in users Senior Center Hospital EsSalud - Tarapoto. April to August 2012. To this end, a study simple descriptive, cross-sectional; prospective, the study population was 385 users Senior Center, calculating a sample of 67 members selected by simple random probábility sampling. The measuring instrument used was a questionnaire developed by Dr. Claudia Trejas Ninosca Castro, applied in a similar study in older adults in Nicaragua and was modified and adapted to the environment in our reality through a pilot applied to 15 users considered in the sample. The main results indicate that users of the Centre for the Elderly have a regular knowledge level (49.2º/o), positive altitudes (52.2%) and prevention practicas prevalent risk practlces (82.1%) in HIV I AIDS. As recommended in the senior cftizen programs also protocoling screening for sexually transmitted diseases, especially HIV/AIDS